The Nature of the Embodiment of "Law" (dhamma/λόγος) in Early Buddhism and Christianity - Divino, Federico (Buddhist Christian studies, 2026)
This paper addresses the conceptual similarities and differences in the embodiment of normative or revealed ideals - that is, the concept of dhamma in early Buddhism and λόγος in early Christianity. Through comparative reading of two introductory scriptural passages - John 14:9-10 of the Gospel of John and SN 22.87 of the Pāli Canon - the paper addresses how Jesus and the Buddha are loci of divine or cosmic law or divine word. The analysis will be especially concerned with the semiotic processes through which these characters become living instantiations of abstract ideals. While both traditions utilize semiosis to communicate foundational truths through the person of a realized figure, Christian λόγος is a unique, ontological instantiation of divine word in Jesus, whereas Buddhist dhamma is functionally embodied by the Buddha as an attainable state of realization, not as a monopoly of divinity. The paper underscores key theological divergences concerning authority, transmission, and embodiment in both traditions, contributing to broader discussions in comparative religion, semiotics, and philosophy.